PERANCANGAN KONSEP PHOTOGRAFI KOMERSIAL SEBAGAI ASPEK KREATIFITAS IKLAN PROMOSI BATIK RUMOH MALAKA - maulana, maulana (VCoDe : Visual Communication Design Journal, 2025)
Commercial photography used as one of the promotional media. Designers created commercial photography as a creative aspect of the batik product ads of malaka rumoh which is the original batik of the kuta malaka, Big day.Creation process carried out through design thinking method. The stage starts with data collection and analysis gathering, resulting in the concept of a photo shoot. The results of the work were then poured into various media among the prototype billboards, poster, magazines and website markets place. The use of commercial photography is expected to improve the quality of promotion for malaka batik. The role of photography in advertising is crucial to supporting the promotion of a product. I used to be. Advertising done through mouth to mouth, but as the age develops and the technology, Advertising methods also thrive.That's why. The company must establish a proper promotional strategy.kata kunci: Photography Commercial, Batik Rumoh Malaka, Aceh Besar, Promotional Media